Differential relationships between autistic traits and anthropomorphic tendencies in adults and early adolescents - Gao, Rui-Rui; Si, Shang-Wen; Lin, Xiao-Xiao; Wang, Yu-Zheng; Wang, Ning; Wang, Jin-Yan; Luo, Fei (Frontiers in Psychology, 2024)
Anthropomorphism, the attribution of human-like qualities (e.g., mental states) to nonhuman entities, is a universal but variable psychological experience. Adults with professionally diagnosed autism or high levels of subclinical autistic traits consistently show greater tendencies to anthropomorphize, which has been hypothesized to reflect 1) a compensatory mechanism for lack of social connectedness and 2) a persistence of childhood anthropomorphism into adulthood. Here, we directly tested these hypotheses in a general population sample consisting of both adults (N=685, 17–58 years old) and early adolescents (N=145, 12–14 years old) using the refined 9-item Anthropomorphism Questionnaire (AnthQ9), which measures both present and childhood anthropomorphic tendencies. We found that adults with heightened autistic traits reported increased present anthropomorphism (e.g., tend more to perceive computers as having minds), which held even after controlling for social connectedness. In contrast, adolescents with heightened autistic traits did not show increased present anthropomorphism, but rather reported reduced childhood anthropomorphism (e.g., less likely to perceive toys as having feelings) after controlling for social connectedness. We also found evidence that the present and childhood subscales of the AnthQ9 may tap into fundamentally different aspects of anthropomorphism. The results suggest that increased anthropomorphic tendencies in adults with heightened autistic traits cannot be explained solely by increased sociality motivation, but may be due to delayed development of anthropomorphism, although alternative possibilities of measurement problems cannot be ruled out. Implications for the measurement of anthropomorphism and its relation with theory of mind were also discussed.